Avaliação da biocompatibilidade e do efeito no reparo ósseo de um scaffold manufaturado a partir de um material vítreo fibroso - Armelin, Paulo Roberto Gabbai (Universidade Federal de São Carlos, 2015)
Millions of bone fractures occur annually worldwide and the consequent bone repair process is complex, involving many biological events until it reaches the restoration of the tissue integrity. During that process some problems can occur due to delays in the bone healing, which does not allow the proper joining of the tissue. Thus, it is necessary to search for new technologies that work in restoring the integrity of the bone tissue and that promote the osteoconduction and the osteoinduction. In this sense, the use of bioactive materials in the bone repair process is a promising alternative. Following this, two studies (I and II) were developed in order to investigate a new fibrous glassy scaffold, and these studies were based in three lines of research: (i) the characterization of the new fibrous glassy scaffold; (ii) the biocompatibility evaluation of this bioactive material; (iii) the analysis of the biological performance of this new scaffold in the bone repair. More specifically, in the study I the developed scaffolds were characterized in terms of porosity, mineralization and morphological features. Additionally, fibroblast and osteoblast cells were seeded in contact with extracts of the scaffolds to assess cell proliferation and genotoxicity after 24, 72 and 144 h. Finally, scaffolds were placed subcutaneously in rats for 15, 30 and 60 days. In regards to study II, the morphological structure of the scaffolds upon incubation in phosphate buffered saline (PBS) (via scanning electron microscope) was assessed after 1, 7 and 14 days and, also, the in vivo tissue response to the new biomaterial was evaluated using implantation in rat tibial defects. The histopathological, immunohistochemistry and biomechanical analyzes after 15, 30 and 60 days of implantation were performed to investigate the effects of the material on bone repair. The scaffolds presented interconnected porous structures (porosity of ~75%), and the precursor bioglass could mineralize a hydroxycarbonate apatite (HCA) layer in SBF after only 12 h. The PBS incubation indicated that the fibers of the glassy scaffold degraded over time. With regards to the biological investigations, the biomaterial elicited increased fibroblast and osteoblast cell proliferation, and no DNA damage was observed. The in vivo experiment showed degradation of the biomaterial over time, with soft tissue ingrowth into the degraded area and the presence of multi-nucleated giant cells around the implant. At day 60, the scaffolds were almost completely degraded, and an organized granulation tissue filled the area. Additionally, the histological analysis of the implants in the bone defects revealed a progressive degradation of the material with increasing implantation time and also its substitution by granulation tissue and woven bone. Histomorphometry showed a higher amount of newly formed bone area in the control group (CG) compared to the biomaterial group (BG) 15 days post-surgery. After 30 and 60 days, CG and BG showed a similar amount of newly formed bone. The novel biomaterial enhanced the expression of RUNX-2 and RANK-L, and also improved the mechanical properties of the tibial callus at day 15 after surgery. These results indicate that the new fibrous glassy scaffold is bioactive, non-cytotoxic, biocompatible and promising for using in bone tissue engineering.
Biocompatibilty of a scaffold obtained from a fibrous glassy material and its effect on bone repair
Keywords: Caracterização; Biocompatibilidade; Biomaterial; Vidro bioativo; Scaffold fibroso; Reparo ósseo; Citotoxicidade; Characterization; Biocompatibility; Biomaterial; Bioactive glass; Fibrous scaffold; Bone repair; Cytotoxicity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL